2020
DOI: 10.1055/a-1255-3161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sprint Duration during Minimal Volume Exercise on Aerobic Capacity and Affect

Abstract: The aims of this study were to investigate the influence of reduced-exertion, high-intensity interval training (REHIT), comparing a novel shortened-sprint protocol (SSREHIT) against a traditional protocol (TREHIT), on perceptual responses and to determine if changes in peak oxygen uptake (V˙O2peak) are attenuated with shorter sprints. Twenty-four healthy men undertook 15 sessions of SSREHIT or TREHIT. V˙O2peak was determined at baseline and after completion of each exercise condition. Affective (pleasure-displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In addition, we observed that the participants provided higher ratings on the FS (indicating more pleasure) in the control condition than in the SSREHIT condition (i.e., after exercise and at posttest). However, our ratings in the SSREHIT condition are comparable to other studies performing SSREHIT (up to 8 × 5-s “all-out” effort sprints; ~37 s recovery between sprints) in healthy younger adults [ 19 , 22 ] and middle-aged adults with nondiabetic hyperglycemia [ 21 ]. In this context, it should be noted that the mean ratings on the FS immediately after exercise and posttest remained positive (1.40 and 1.55—correspond to “fairly good”), suggesting that SSREHIT does not induce strong displeasure.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, we observed that the participants provided higher ratings on the FS (indicating more pleasure) in the control condition than in the SSREHIT condition (i.e., after exercise and at posttest). However, our ratings in the SSREHIT condition are comparable to other studies performing SSREHIT (up to 8 × 5-s “all-out” effort sprints; ~37 s recovery between sprints) in healthy younger adults [ 19 , 22 ] and middle-aged adults with nondiabetic hyperglycemia [ 21 ]. In this context, it should be noted that the mean ratings on the FS immediately after exercise and posttest remained positive (1.40 and 1.55—correspond to “fairly good”), suggesting that SSREHIT does not induce strong displeasure.…”
Section: Discussionsupporting
confidence: 84%
“…Collectively, the above-mentioned evidence suggest that shortened SIT protocols (e.g., 8 × 5 s), being termed as “shortened-sprint reduced exertion high-intensity training” (SSREHIT), are, from a psychological point of view, more suitable for an exercise intervention than the classical SIT protocol (i.e., Wingate protocol). Given the time-efficiency of SIT (as compared to continuous moderate-intensity exercises) in general and the better psychological characteristics of SSREHIT (as compared to classical SIT using the Wingate protocol) in particular, SSREHIT can be considered as a promising exercise modality being worth future investigations [ 19 , 21 , 22 ]. Interestingly, the current research has demonstrated that SSREHIT elicits substantial benefits in markers of cardiorespiratory fitness and metabolic health in healthy people [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed that the participants provided higher ratings on the FS (indicating more pleasure) in the control condition than in the SIT condition (i.e., after exercise and at post-test) while our ratings in the SSREHIT condition are comparable to other SSREHIT studies [14,16,17]. In this context, it should be noted that the mean rating on the FS immediately after exercise and before post-test remained positive (1.40 and 1.55 -correspond to "fairly good") suggesting that SSREHIT does not induce strong displeasure.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, the ndings of a recent study suggest that a reduction of the sprint time from 20 seconds to 5 seconds is favorable when psychological parameters such as affect, effort, and enjoyment were considered [14]. Given that psychological parameters such as enjoyment are important factors predicting long-term adherence to physical exercise interventions [15], it seems reasonable to assume that the investigation of the effects of SIT protocols with a shorter sprint time duration (termed as "shortenedsprint reduced exertion high-intensity training" [SSREHIT]) can be considered as a promising eld for future research [14,16,17].…”
Section: Introductionmentioning
confidence: 99%